Ruling by Favors: Prison Guards' Informal Exercise of Institutional Control. Issue 2 (25th April 2012) - Ibsen, Alexander Z.
<x xml:space="preserve">Abstract</x> This ethnographic research addresses the control strategies employed by Norwegian guards in everyday interactions with inmates under institutional conditions in which the use of official negative sanctions is restricted. The article explains how a complicated informal system of favors develops that forms a new basis for punishment through the withdrawal of rewards. By distributing favors liberally, giving an inmate only what he is entitled to serves as a substitute for negative sanctions. Inmates are not opposing the informal system, and its effect on ensuring institutional control does not challenge the intentions of formal prison rules. Still, the informal system must be monitored and protected against overuse by inmates and must also be kept hidden from the officials making up the prison administration who oppose all departures from the official rules.